Young People Who Display Harmful Sexual Behaviors and Their Families: A Qualitative Systematic Review of Their Experiences of Professional Interventions. (July 2020) - Campbell, Fiona; Booth, Andrew; Hackett, Simon; Sutton, Anthea
It is estimated that 30–50% of all childhood sexual abuse involves other young people as perpetrators. The treatment of harmful sexual behavior (HSB) in young people has evolved from interventions developed for use with adult perpetrators of sexual offenses. Increasingly, these approaches were not seen as appropriate for use with young people. The purpose of this qualitative systematic review was to establish what intervention components are viewed as acceptable or useful by young people and their families in order to inform the development of interventions for young people with HSB. We conducted searches across 14 electronic databases as well as contacting experts to identify relevant studies. Thirteen qualitative studies were included in the analysis, reporting findings from intervention studies from the United Kingdom, United States, New Zealand, Australia, and Ireland. Thematic analysis was used to combine findings from the studies of young people and parent/carers views. Five key themes were identified as critical components of successful interventions for young people with HSB. These included the key role of the relationship between the young person and practitioner, the significance of the role of parents and carers, the importance of considering the wider context in which the abuse has occurred, the role of disclosure in interventions, and the need to equip young people with skills as well as knowledge. The evidence was limited by the small number of studies that were mainly from the perspectives of adolescent males.